Creating Model of Sustainable Performance based Green Management System on The Small and Medium Enterprises - Putri, Vini Wiratno; Sudarma, Ketut (Universitas Negeri Semarang, 2020)
The aims of this paper is to analyze the effect of the relationship between knowledge and on green management and its implication on competitive advantage and sustainable performannce. This study used a quantitative research approach that explains the phenomenon by collecting numerical data analyzed using structural equation modelling (SEM) with the WarpPLS program application. The population in this study were small or medium business owners (general managers) in the industrial sector in the city of Semarang. Knowledge and green management have a significant effect on competitive advantages and competitive advantages has a significant effect on the sustainability performance. It means that the knowledge and green management simultaneously shows a significant effect on competitive advantages and sustainability performance. The application of green management will also improve sustainability performance. The originality of this study is on the testing of simultaneous relationships between the factors making up the application of green management, namely knowledge as well as the impact of green management implementation on sustainability performance.